The Effectiveness of Acupressure in First Trimester Pregnant Women with Emesis Gravidarum at TPMB Nurseha in 2023 - Olivia Nency; Nurseha Nurseha (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Pregnant women with emesis gravidarum who use acupressure can reduce or even avoid the use of anti-nausea drugs which have the potential to have side effects. This can be considered as an effective non-pharmacological alternative in treating emesis gravidarum. Purpose of Writing: Knowing the Effectiveness of Acupressure in First Trimester Pregnant Women with Emesis Gravidarum at TPMB Nurseha in 2023. Research Method : This research is a quasi-experimental research with pretest posttest with control group design. The independent variable in this study is doing acupressure and the dependent variable is Emesis Gravidarum. taken by purposive sampling. Data analysis was carried out univariately and bivariately, to find out differences in Emesis Gravidarum level scores at the pretest and posttest in each treatment group using the Paired t-test, if not normally distributed then use the Wilcoxon. Research Results: Based on research results it is known that Asymp. Sig (2 – Talled) in the intervention group is 0.000 because 0.000 <0.05, it can be concluded that the hypothesis is accepted. This means that there is a difference before and after acupressure is done on emesis gravidarum. While the results of the study found Asymp. Sig (2 – Talled) in the control group is 0.163 because 0.163 > 0.05, it can be concluded that the hypothesis is rejected. This means that there is no difference before and after acupressure on emesis gravidarum. So it can be concluded that there is Effectiveness of Acupressure in First Trimester Pregnant Women with Emesis Gravidarum at TPMB Nurseha in 2023.